Combining Actual and Contingent Behavior to Estimate the Value of Sports Fishing in the Lagoon of Venice - Anna Alberini; Valentina Zanatta; Paolo Rosato (Fondazione Eni Enrico Mattei (FEEM), 2005)
This paper reports the results of a Travel Cost Method (TCM) study about the recreational use of the Lagoon of Venice for sports fishing. In April-July 2002, we conducted a mail survey of anglers with valid licenses fishing on the Lagoon of Venice to gather data on their fishing trips, behaviors and expenditures over the previous year. We also asked questions about trips that would be undertaken under hypothetical changes in the price of a trip and/or in the catch rate. Actual and hypothetical trips are combined to estimate single-site TCM demand function for trips. We propose several models to test whether it is acceptable to pool hypothetical and actual trip data, focusing on the respondent heterogeneity in the contingent behavior questions. Our models suggest actual and contingent behavior are driven by the same demand function, and can be pooled for estimation purposes. We use this estimated demand function, and its shift when the catch rate is improved, to compute angler surplus at the current catch rate and the change in surplus accruing from a 50% improvement in the catch rate. For the average angler in our sample, the former is about exteuro1,700 a year, while the latter is about exteuro2,800.
Keywords: Q26; Q51; 330; Sports fishing value; Travel cost method; Environmental improvement; Fischereisport; Reisekostenansatz; Wohlfahrtsanalyse; Venedig; Italien